Pemanfaatan Birth Ball Pada Ibu Hamil di PMB Muzilatul Nisma Kota Jambi - Selpyani Sinulingga; Sirly Patriani (Jurnal Abdimas Kesehatan (JAK), 2022)
Birth Ball is one of physical therapy or simple exercises with a ball. Birth Ball is applied to pregnant women ,maternity mothers and postpartum mothers. The Independent Midwife Practice (PMB) Muzilatul Nisma is one of the health care facilities in Jambi City that provides midwifery services such as Mom's and Baby Spa services with certified midwives/therapists. One of the available therapies is Birth Ball therapy. Based on the preliminary survey, most of the pregnant women who visited did not get adequate information about birth ball and the utilization of birth ball for pregnant women. The purpose of this activity is to increase the knowledge and skills of pregnant women about the utilization of Birth Balls in pregnancy. The target of this activity is carried out on pregnant women in the second and third trimesters. The activities are the implementation of pre-test, providing education by giving leaflets, demonstration of the utilization of Birth Ball and post-test implementation. The result there is an increase knowledge up to 43.35%. With this educational activity and the utilization of Birth Ball, it is hoped that the feeling of comfort and pain reduction increases during pregnancy and before maternity to support the realization of normal maretnity, safe maternity, comfortable maternity and fluent maternity.